Socio-phenomenological perspective of the bureaucratic organizational structure - Cuenú Cabezas, Jairo E. (Cuadernos de Administración, 2011)
To accomplish their purposes in carrying out their activities, organizations need a structure. The word structure is used by different disciplines, which – in general terms – conceive it as an order-relation. In organizational theory, the word structure essentially defines the relationships amongst individuals to reach a given end. The organizational structure is a product of the interaction of human beings and it is they, from their experiences, rationalities, and expectations, who determine how the purposes should be accomplished. Different forms exist, in terms of structure, to accomplish organizational purposes; one of the most representative forms is the bureaucratic approach. Bureaucracy is a method to use special abilities. This cannot be denied, but it is also a form, from Alfred Schütz’ phenomenological sociology, of establishing settings of intimacy and anonymity in organizational relations. The objective of this article is to show how the bureaucratic structure generates intimacy or anonymity in the organization. In the first place, the article presents the concept of structure from which the organizational structure is explained, especially the bureaucratic structure. The second part presents Alfred Schütz’ phenomenological sociology, emphasizing on the concept he raised of the world of everyday life and the relations of otherness. With the aforementioned, intimacy and anonymity in the organization is developed or explained. In conclusion, among other aspects, we address the need for the organizational theory or for organizational theorists to approach everyday life in organizations.